Cytoreductive nephrectomy in the modern era: Predictors of use, morbidity, and survival - Minnillo, Brian J.; Tabayoyong, William; Francis, John J.; Maurice, Matthew J.; Zhu, Hui; Kim, Simon; Abouassaly, Robert (Canadian Urological Association Journal, 2017)
Introduction: To determine tumour, patient, and provider factors associated with cytoreductive nephrectomy (CN) use and to identify those factors that predicted short-term and long-term surgical outcomes. Methods: We performed a retrospective review (1998‒2011) of the National Cancer Database, a U.S. population-based oncology outcomes database. The review included 36 549 patients with metastatic renal cell carcinoma (mRCC). We assessed predictors of CN use, length of stay (LOS), 30-day readmission, and 30-day mortality using multivariable logistic regression. The Cox proportional hazards model assessed predictors of overall survival (OS). Results: Overall, 10 809 (29.6%) patients received CN, increasing from 15.2% to 36.1% over time. Private insurance (odds ratio [OR] 1.26; 95% confidence interval [CI] 1.16‒1.37) and academic facilities (OR 1.83; 95% CI 1.68‒1.99) were associated with receiving CN (p<0.0001). Charlson score ≥2 and older age group were less likely to undergo surgery (p<0.0001). Median LOS was five days (interquartile range [IQR] 3‒7), while 30-day readmission and 30-day mortality were 5.3% and 3.3%, respectively. Undergoing CN (hazard ratio [HR] 0.48; 95% CI 0.44‒0.52; p<0.0001) and treatment at academic centres (HR 0.88; 95% CI 0.81‒0.95; p=0.001) were independently associated with improved OS. Limitation includes retrospective design with possible selection bias. Conclusions: Increased CN use continues in the modern era, with relatively low surgical morbidity. Further study is required to determine if the finding of lower all-cause mortality in patients treated at academic centres is due to improved care or unmeasured confounders.